Bone Marrow Stromal Cells Rescue Ischemic Brain by Trophic Effects and Phenotypic Change Toward Neural Cells. (January 2015) - Shichinohe, Hideo; Ishihara, Takeshi; Takahashi, Koji; Tanaka, Yoshikazu; Miyamoto, Michiyuki; Yamauchi, Tomohiro; Saito, Hisayasu; Takemoto, Hiroshi; Houkin, Kiyohiro; Kuroda, Satoshi
Background. Transplantation of bone marrow stromal cells (BMSCs) may contribute to functional recovery after stroke. This study was designed to clarify their mechanisms, trophic effects of neurotrophic factors, and neural differentiation. Methods. Mouse neurons exposed to glutamate were cocultured with mouse BMSCs. Either neutralizing antibodies against brain-derived neurotrophic factor (BDNF) or nerve growth factor (NGF) or Trk inhibitor K252a was added to explore the mechanism of their protective effects. Fluorescence in situ hybridization (FISH) was used to assess BDNF or NGF mRNA expression in BMSCs. The mice were subjected to permanent focal ischemia, and 7 days later, either BMSCs or the vehicle was stereotactically transplanted into the ipsilateral striatum. The mouse brains were processed for FISH and immunostaining 2 or 4 weeks after transplantation. Results. BMSCs significantly ameliorated glutamate-induced neuronal death. Treatment with anti-BDNF antibody significantly reduced their protective effects. FISH analysis showed that the majority of BMSCs expressed BDNF and NGF mRNA in vitro . BMSC transplantation significantly improved the survival of neurons in peri-infarct areas. FISH analysis revealed that approximately half of BMSCs expressed BDNF and NGF mRNA 2 weeks after transplantation; however, the percentage of BDNF and NGF mRNA-positive cells decreased thereafter. Instead, the percentage of microtubule-associated protein 2–positive BMSCs gradually increased during 4 weeks after transplantation. Conclusions. These findings strongly suggest that BDNF may be a key factor underlying the trophic effects of BMSCs. BMSCs might exhibit the trophic effect in the early stage of cell therapy and the phenotypic change toward neural cells thereafter.